Level of endosulfan among women in Talwandi Sabo Block of Southern Punjab, India - Noopur Sharma; Roumi Deb; Ratika Samtani (Wolters Kluwer Medknow Publications, 2019)
Endosulfan is one of the most prevalent organochlorine pesticides used in the agricultural sector in the developing countries including India. It affects the physiological functioning of different organ systems including nervous, immune, hepatic, and reproductive system. Realizing the safety and health concern, restrictions have been imposed at various levels, but the usage has still continued in the plantation crops. Owing to pesticide beneficiary of north India, the cotton belt commonly called the Malwa region of Punjab was evaluated for identifying the levels of Endosulfan in the blood samples of women working in agricultural fields. Gas chromatograph with electron capture detector was used for detecting the levels of endosulfan metabolites among twenty active female workers. The mean level of endosulfan recorded in the tested population was observed to be 2.22 ppb. It is difficult to draw a certain conclusion based on these findings because the subjects were less in number. However, detection of even very low concentrations of endosulfan residues signifies its continued accessibility to the women population. Encouragement of more such population-based research needs to be adopted to determine the body burden of such pesticides in humans. The effective implementation of the ban on Endosulfan could be checked by a combined retrospective and prospective study to infer a justifiable impact.